Revamping Law by Circumventing the State. Non-governmental organizations in the international management of social violence on the African continent - (:unkn) unknown (My University, 2011)
This thesis explores the social usages of the law in scholarly and professional spaces, in the North, that are sites of production and legitimation of tools devised to diagnose and prescribe solutions over armed conflicts on the African continent since the end of the Cold war. Based on the hypothesis of the “weak” character of an internationalized space of conflict management, it aims at tracing the triggers and logic of a “sens commun réformateur” over armed conflicts in the South, expressed in a three-pronged emphasis over prevention, pacification and punishment. It favors an empirical entry, the usages of the law by non-governmental organizationsbased in the United States and Western Europe. Its focus is restricted to social usages of the law ranging from the legitimation of military interventions to para-judicial tools such as “Alternative dispute resolution” to judicial international arenas. Divided in three parts, it traces firstly, the genesis and turn, expressed in policy and scholarly discourses and practices, towards a political economy of intervention, justified as triggered by the diagnosed failure of the recipient State in the African South, and articulated with a redefinition of intervention as a continuum ranging from prevention to military interventions. It shows, secondly, how non-governmental forms of intervention have beenintegrated within this redefinition of intervention as a modality not only of circumventing recipient States, but also of rebuilding social peace in the South, i.e. of building a “bottom up” State, and analyzes the redefinition of forms of legitimation of non-profit modalities of interventionism. It explores, thirdly, the instrumental role played by the law as a symbolic capital and a moral resource in accommodating a tension between constraint, including in the moral and legal arsenal deployed to justify military interventions, and order, in that the effect is one of legitimation within objectified
Keywords: African Research